ANALISA KELUAR REL KERETA API - Atmadja, Sugeng Tirta (ROTASI, 2001)
journey beside that, â€œderailmentâ€ that caused high speed can threaten passengerâ€™s life. There are two cases willbe discussed :1. â€œKontel-momentâ€ consequence centrifugal force when train to be in motion on rail-road which has bend archwith certain radius.2. â€œQuasi static effectâ€ that cause derailment.